KEARIFAN LOKAL MASYARAKAT SUKU SASAK LOMBOK DALAM MEMANFAATKAN TUMBUHAN BERPOTENSI OBAT DI WILAYAH KABUPATEN LOMBOK TIMUR SEBAGAI SUMBER BELAJAR ETNOBOTANI - Fajri, Nurul (Cocos Bio, 2020)
Nowadays people are increasingly aware of the importance of returning to nature to cure various diseases. Increased awareness. so scientific research is increasingly directed at natural ingredients. Herbal medicines that are processed in a modern way and are supported by research results are increasingly available. The use of traditional medicine has long been practiced in developing countries and developed countries. The use of various types of plants is influenced by ethnic groups or ethnic level culture. Exploring the perceptions and conceptions of traditional community knowledge about the plants around them is an activity of gathering local wisdom with the local community. Interactions between humans and plants are studied through ethnobotany studies. The purpose of this study was to determine the potential use of medicinal plants by the East Lombok Sasak etnic and the use of research results as a source of ethnobotany learning. The method used is ethnometodology.  The results of the research have been obtained 32 types of potentially medicinal plants that are often used by the Sasak people of East Lombok Regency to treat various diseases. Utilization by processing the parts of plants, namely leaves, fruit, seeds, stems and roots. The results of this study will continue to be used as a source of ethnobotany learning